Judges’ Private Lives and the Risk of Conflicts of Interest: A Normative Analysis of the Code of Ethics and Judges’ Rules of Conduct (KEPPH) - Tanu Djaja; Chung Shen Orlando Honggowibowo (LPPM of NAROTAMA UNIVERSITY, 2026)
The personal lives of judges and the attendant risk of conflicts of interest pose a critical threat to judicial independence, impartiality, and public trust in Indonesia’s judiciary. This normative legal study assesses the Indonesian Code of Ethics and Conduct for Judges (KEPPH) using statutory, conceptual, and comparative methods, with particular reference to the Bangalore Principles of Judicial Conduct. The research examines how KEPPH addresses intersections among judges’ personal finances, family ties, and professional duties, and reviews enforcement practice through decisions of the Judicial Commission, the Supreme Court, and the Judges’ Honor Council. Findings indicate that, while KEPPH establishes a comprehensive normative framework prohibiting judges from adjudicating matters involving personal interests, substantial gaps in implementation remain. Key vulnerability areas identified include financial interests, business activities and ancillary positions, familial relationships, and political affiliations that may create actual or perceived conflicts of interest. Comparative analysis with Netherlands, Singaporean, and Malaysian standards shows substantive alignment with international best practices but highlights weaknesses in enforcement—especially in financial disclosure, oversight of secondary employment, and institutional coordination between internal and external supervisory bodies. The study concludes that strengthening internal–external supervision, adopting risk-based oversight, enhancing transparency through systematic financial reporting, promoting merit-based judicial appointment processes, and instituting continuous professional ethics education are necessary to protect judicial independence and sustain public confidence in Indonesia’s judiciary.